2014
DOI: 10.5761/atcs.oa.13-00028
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal Lymph-nodes Metastasis beyond the Lobe-specific: An Independent Risk Factor toward Worse Prognoses

Abstract: Purpose: Five-year survival rates were widely dispersed in pN2 non-small cell lung cancer (NSCLC). The present study aims to investigate the prognosis of patients with lymph node metastasis beyond lobe-specific mediastinal regions. Methods: A total of 654 pathologically proved N2-NSCLC patients were enrolled. All patients underwent a major pulmonary resection and radical mediastinal lymphadenectomy. Two separate groups were assigned according to the definition of lobe-specific nodal metastasis: Group LS (lobe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…This result compares favourably to the study by Riquet et al [26]. Sun and colleagues demonstrated that the survival in patients with lymph node metastasis beyond lobe-specific nodes had a significantly worse prognosis with median survival and 5-year survival of 24 months and 11.7% [28]. Collectively, our study and others do not support a lobe-specific lymphadenectomy as advocated by other groups [5,29].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This result compares favourably to the study by Riquet et al [26]. Sun and colleagues demonstrated that the survival in patients with lymph node metastasis beyond lobe-specific nodes had a significantly worse prognosis with median survival and 5-year survival of 24 months and 11.7% [28]. Collectively, our study and others do not support a lobe-specific lymphadenectomy as advocated by other groups [5,29].…”
Section: Discussionsupporting
confidence: 62%
“…This concept of a 'fixed' lymphatic drainage path is the underlying premise to perform a lobe-specific lymphadenectomy. Upper lobe tumours usually drain to the lymph nodes of the upper mediastinum (stations 2-6), and middle and lower lobe tumours drain to nodes in the lower mediastinum (stations 7-9) [5,28]. An important observation of our study is that 16% of clinically node-negative, stage I NSCLC patients had N2 disease that did not follow a lobe-specific lymphatic drainage pattern.…”
Section: Discussionmentioning
confidence: 56%
“…This result deserves further consideration, but might have been biased by selection of patients with 19) Several studies have found that multi-level N2 involvement and number of involved nodal zones are poor prognostic factors for survival in pN2 NSCLC patients, as indicated by the IASLC staging project. 20,21) In contrast, single-level N2 involvement is a favorable prognostic factor even in patients with bulky, namely greater than 2 cm in short-axis diameter, N2 NSCLC. 22) However, our results showed overlap of survival curves for single-and multi-level N2 NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to realise that the concept of lobe-specific systematic nodal dissection is based on statistics, on the probability of nodal involvement depending on the lobar location of the tumour, but it is not exact [139][140][141]. Involved lymph nodes may remain beyond the nodal stations explored, and their presence has a deleterious effect on prognosis [142]. Lobe-specific systematic nodal dissection certainly is better than no nodal dissection at all, but systematic nodal dissection is the only procedure that ensures an accurate staging and the probability of prolonged survival for the individual patient.…”
Section: Intrathoracic Staging At Pulmonary Resectionmentioning
confidence: 99%